2023
DOI: 10.1371/journal.pone.0284750
|View full text |Cite
|
Sign up to set email alerts
|

Structural and haemodynamic evaluation of less invasive surfactant administration during nasal intermittent positive pressure ventilation in surfactant-deficient newborn piglets

Abstract: The most recent approaches to the initial treatment of respiratory distress syndrome (RDS)- involve non-invasive ventilation (NIV) and less-invasive surfactant (SF) administration (LISA). Combining these techniques has been proven a useful treatment option for SF-deficient neonates. The objective of this study was to explore the impact on the brain (using cerebral near infrared spectroscopy, NIRS) of different LISA methods during NIV, using nasal intermittent positive pressure ventilation (NIPPV) for treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…9 Consistently, NIPPV has been found to be more effective than NCPAP in preventing MV 10 and extubation failure, 11 and previous studies demonstrated that surfactant treatment with LISA technique during NIPPV was effective in both an animal model 12 and very preterm infants. 13 Thus, we hypothesized that the benefits of NIPPV over NCPAP might also affect the time period of surfactant administration during the LISA procedure and that the delivery of a proper TV can allow a better surfactant lung deposition and distribution. To evaluate this hypothesis, we planned a randomized controlled trial in which we compared the effect of using NIPPV versus NCPAP during LISA on respiratory outcome in very premature infants with RDS (NIPAL study: NIPPV vs. NCPAP during Less invasive surfactant administration).…”
Section: Introductionmentioning
confidence: 99%
“…9 Consistently, NIPPV has been found to be more effective than NCPAP in preventing MV 10 and extubation failure, 11 and previous studies demonstrated that surfactant treatment with LISA technique during NIPPV was effective in both an animal model 12 and very preterm infants. 13 Thus, we hypothesized that the benefits of NIPPV over NCPAP might also affect the time period of surfactant administration during the LISA procedure and that the delivery of a proper TV can allow a better surfactant lung deposition and distribution. To evaluate this hypothesis, we planned a randomized controlled trial in which we compared the effect of using NIPPV versus NCPAP during LISA on respiratory outcome in very premature infants with RDS (NIPAL study: NIPPV vs. NCPAP during Less invasive surfactant administration).…”
Section: Introductionmentioning
confidence: 99%